Corticospinal activity during a single-leg stance in people with chronic ankle instability - Masafumi Terada; Kyle B. Kosik; Ryan S. McCann; Colin Drinkard; Phillip A. Gribble (Elsevier, 2022)
Purpose: The aim of the study was to determine whether corticospinal excitability and inhibition of the tibialis anterior during single-leg standing differs among individuals with chronic ankle instability (CAI), lateral ankle sprain copers, and healthy controls. Methods: Twenty-three participants with CAI, 23 lateral ankle sprain copers, and 24 healthy control participants volunteered. Active motor threshold (AMT), normalized motor-evoked potential (MEP), and cortical silent period (CSP) were evaluated by transcranial magnetic stimulation while participants performed a single-leg standing task. Results: Participants with CAI had significantly longer CSP at 100% of AMT and lower normalized MEP at 120% of AMT compared to lateral ankle sprain copers (CSP100%: p = 0.003; MEP120%: p = 0.044) and controls (CSP100%: p = 0.041; MEP120%: p = 0.006). Conclusion: This investigation demonstrate altered corticospinal excitability and inhibition of the tibialis anterior during single-leg standing in participants with CAI. Further research is needed to examine the effects of corticospinal maladaptations to motor control of the tibial anterior on postural control performance in those with CAI.